Synergetic Cobalt‐Copper‐Based Bimetal–Organic Framework Nanoboxes toward Efficient Electrochemical Oxygen Evolution - Cheng, Weiren; Wu, Zhi‐Peng; Luan, Deyan; Zang, Shuang‐Quan; Lou, Xiong Wen (David) (Angewandte Chemie International Edition, 2021)
The development of efficient oxygen electrocatalysts and understanding their underlying catalytic mechanism are of significant importance for the high‐performance energy conversion and storage technologies. Herein, we report novel CoCu‐based bimetallic metal–organic framework nanoboxes (CoCu‐MOF NBs) as promising catalysts toward efficient electrochemical oxygen evolution reaction (OER), fabricated via a successive cation and ligand exchange strategy. With the highly exposed bimetal centers and the well‐designed architecture, the CoCu‐MOF NBs show excellent OER activity and stability, with a small overpotential of 271 mV at 10 mA cm−2 and a high turnover frequency value of 0.326 s−1 at an overpotential of 300 mV. In combination of quasi in situ X‐ray absorption fine structure spectroscopy and density‐functional theory calculations, the post‐formed CoCu‐based oxyhydroxide analogue during OER is believed to account for the high OER activity of CoCu‐MOF NBs, where the electronic synergy between Co and neighbouring Cu atoms promotes the O−O bond coupling toward fast OER kinetics. Cobalt‐copper‐based conductive bimetal–organic framework nanoboxes (CoCu‐MOF NBs) have been synthesized as a promising oxygen electrocatalyst, through a successive cation and ligand exchange strategy. With the bimetallic synergetic effect and the well‐designed hollow architecture, the CoCu‐MOF NBs show excellent electrocatalytic activity and robust long‐term stability toward efficient oxygen evolution electrocatalysis.